Histological Description of the Electroreceptors and Other Key Tissues in the Black Ghost Knifefish, Apteronotus albifrons - Hutheyfa Al-Salih; Ammar A. Issa; Ilham J. J. Alshami; Hussein A. Saud; Gregory paull (Kufa Journal for Veterinary Medical Sciences)
Black ghost knifefish is a unique model for studying many biological aspects such as development of electroreceptors, which help in determining the evolutionary history among species on the one hand, and on the other hand explains the mechanisms used by these species to communicate with each other. In this study, we described tissues of some organs in Black ghost knifefish Apteronotus albifrons that included the gills, liver, kidney, oesophagus, vertebrae, spinal cord and electroreceptors. The study characterized the electroreceptors that embedded in the skin in this species for the first time. The histological examination using Haematoxylin and Eosin stains reveals that this type of electroreceptors is tuberous